Strengthening maternal health: gestational diabetes screening as a national priority - Ayesha Ali (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Gestational diabetes mellitus (GDM) is a condition of growing concern in Pakistan, carrying significant implications for both maternal and neonatal health outcomes in Pakistan and globally. GDM is a known risk factor for gestational hypertension, which can progress to complications such as proteinuria, dyslipidaemia, thrombocytopenia, and pulmonary oedema, ultimately resulting in preeclampsia.1 According to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria, the global prevalence of GDM is 14.7.2 A recent study has reported that the overall prevalence of GDM in Pakistan is estimated to be around 16.7%, with many remaining undiagnosed owing to lack of standardized screening protocols.3 This gap in early detection is highly alarming and requires urgent attention, since timely intervention could substantially reduce the risk of the perinatal complications.4 Therefore, it is essential that both healthcare providers and policymakers prioritise screening for gestational diabetes mellitus as a vital component in the national health strategy, which should be implemented without delay. A study that was conducted with 210 doctors reported in major cities across Pakistan that there were no uniform criteria used for diagnosis. 61.4% reported using the WHO criteria for diagnosis, 12.4% used the American Diabetes Association criteria, 9% of respondents used the IADPSG criteria, and 17.1% of respondents were unsure of the screening criteria they were using.5 This study highlights the urgent need for a standardized nationwide protocol for GDM screening – which should be integrated into routine antenatal care, as a matter of priority particularly primary healthcare centers. Healthcare providers receive training in the diagnosis and management of GDM, alongside targeted awareness campaigns for women regarding the risks associated with uncontrolled blood glucose levels during pregnancy. These awareness campaigns could help be highly beneficial for women of childbearing age to promote early screening and encourage healthy practices during pregnancy. As the incidence of diabetes in the general population continues to rise in Pakistan, so too does the urgency for routine GDM screening. As Pakistan faces an incredibly high disease burden for diabetes - this burden is also further reflected in its pregnant population. A standardized screening approach, offering screening to all pregnant women, regardless of risk factors -would ensure that no case of GDM goes undetected. Implementation and awareness measures pertaining to gestational diabetes mellitus are the need of the hour for improved maternal and neonatal health outcomes across Pakistan.